A rare waterborne outbreak of Bacillus paranthracis in Shandong province, China, 2020: epidemiologic survey, genomic insights, and virulence characteristics - Shuang Wang; Hengjie Xie; Lu Liu; Lei Du; Fang Yin; Yuzhen Chen; Ziqing Liu; Gaoxiang Sun; Xiaomei Zhang; Dapeng Sun; Ming Fang; Lixiao Cheng; et al. (Emerging Microbes and Infections, 2024)
Bacillus paranthracis, a Gram-positive conditional pathogen of Bacillus cereus group species, is capable of causing foodborne and waterborne illnesses, leading to intestinal diseases in humans characterized by diarrhoea and vomiting. However, documented cases of B. paranthracis infection outbreaks are rare in the world, and the genomic background of outbreak strains is seldom characterized. This study retrospectively analyzed strains obtained from an outbreak in schools, as well as from water systems in peri-urban areas, China, in 2020. In total, 28 B. cereus group isolates were retrieved, comprising 6 from stool samples and 22 from water samples. Epidemiological and phylogenetic investigations indicated that the B. paranthracis isolate from drinking water as the causative agent of the outbreak. The genomic comparison revealed a high degree of consistency among 8 outbreak-related strains in terms of antimicrobial resistance gene profiles, virulence gene profiles, genomic content, and multilocus sequence typing (MLST). The strains related to the outbreak show highly similar genomic ring diagrams and close phylogenetic relationships. Additionally, this study shed light on the pathogenic potential and complexity of B. cereus group through its diversity in virulence genes and mice infection model. The findings highlight the usefulness of B. paranthracis genomes in understanding genetic diversity within specific environments and in tracing the source of pathogens during outbreak situations, thereby enabling targeted infection control interventions.